PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI UNIT DESA ( KUD) SETIA KAWAN DESA SUKA DAMAI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Arlina Sandi; Caska ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is done by the cooperative of village unit (KUD) Setia Kawan with the aim to know the influence of service quality to the satisfaction of members of Village Village Cooperative (KUD) Setia Kawan Village Suka Damai Singingi Hilir Subdistrict Kuantan Singingi Regency. The population in this research is all members of village unit cooperative (KUD) Setia Kawan Desa Suka Damai which amounts to 604 members. Sampling in this study was obtained using the method simple random sampling of 86 people. Technique of collecting is done through questionnaire technique and using primary and secondary. The data were analyzed by hypothesis using simple linear regression, partial test (t test), Coefficient of Determination (R2). There are 2 variables, namely service quality and members satisfaction. This means that the independent variables together affect the dependent variable. Furthermore, based on partial test (t test) it can be seen that only service quality variables that affect members satisfaction is indicated by its significance 0,272 while other variables have no effect.Keywords: Service Quality, Members Satisfaction